Risk management of musculoskeletal disorders and ergonomic risk factors in bakery manufacturing industry - Siti Nor Hidayah, Nordin (2017)
A cross-sectional study of risk management at bakery industry was conducted to identify the ergonomic risk factors in the work processes, the prevalence of MSDs among workers and its relationship with the ergonomic risk factors. A total of 44 bakery workers took part in the study. Methodology used in this study involving questionnaire to analyze prevalence of MSDs. Postural analysis was done to determine risk level of posture. While checklist used to determine the associated ergonomic risk factors. This study shows the higher prevalence occurred in slicing and wrapping last product (neck=38.1 %), (wrist/hand=45.0%), (shoulders=28.6 %), (upper back=47.1 %) and (hips/thigh =42.9%) due to combination of lifting object above shoulder level, lifting object >30 em horizontally and repetitive motion. Baking and decoration had the lowest prevalence of body pain (wrist/hand=25.0%), (elbow=35.0%) and neck (28.6%). Respondents' age, gender and duration of employment significantly influenced the prevalence of MSD at all body region. This study shows the workers were experiencing mostly the upper limb as compared to lower limb. Therefore, bakery should take into account by providing proper handhold, educate correct siting and standing techniques and also implement job rotation.